Goals of care documentation by medical oncologists and oncology patient end‐of‐life care outcomes. Issue 18 (22nd July 2022) - Epstein, Andrew S.; Riley, Michael; Nelson, Judith E.; Bernal, Camila; Martin, Steven; Xiao, Han
Abstract : Background: Goals of care (GOC) documentation is important but underused. We aimed to improve oncologist GOC documentation and end‐of‐life (EOL) care. Methods: In April 2020, our cancer center launched a GOC note template, including optional fields for documenting discussion with the patient about: cancer natural history, goals, and/or EOL (resuscitation preferences, hospice receptivity). Associations between GOC notes and EOL care were evaluated. Results: Among 1721 patients dying between June 1, 2020 and June 30, 2021, median days from first GOC note (± with documentation of EOL discussion) to death was 92, whereas a GOC note including EOL discussion ("GOC EOL note"), specifically, was 31. Patients with a first GOC note >60 days before death spent fewer days inpatient (6.7 vs 10.6 days, p < .001). Among patients with GOC EOL notes, those with such documentation >30 days before death had fewer inpatient (5 vs 11, p < .001) and intensive care unit days (0.5 vs 1.5, p < .001), more hospice referrals (57% vs 44%, p = .003), and less chemotherapy ≤14 days before death (6% vs 11%, p = .010). Of 925 admissions of patients dying within ≤30 days, those with GOC EOL notes were shorter (7 vs 9 days, p = .013) but not associated with more hospice discharge (30% vs 25%, p = .163). Oncologist (vs nononcologist) GOC documentation and earlier documentation of EOL discussion were associated in subset analyses with less inpatient care and more hospice referrals. Conclusions: Documentation of GOC, including EOL discussions, is associated with favorable performance on accepted indicators of quality EOL care. Abstract : Electronic health record documentation of goals of care (GOC), including end‐of‐life (EOL) discussions, on a piloted GOC note template, is associated with favorable performance on accepted indicators of quality EOL care. Future research should examine the portability of these and related initiatives as well as their impact on additional metrics important to cancer patients, their families, clinicians, and health systems.